PELATIHAN LITERASI KEUANGAN PETANI LAHAN KERING DI DESA KARANGBAYAN KABUPATEN LOMBOK BARAT - I Ketut Budastra; Taslim Sjah; I Gusti Lanang Parta Tanaya; Halil Halil; Made Aditya Budastra (Universitas Mataram, 2022)
Financial literacy is one aspect of human life capital with regard to the basic ability to be able to make financial decisions appropriately and efficiently so that it has a positive impact on the welfare of individuals and their families. A large number of members of the lower classes of society, such as farmers, micro-entrepreneurs, and informal workers, are suspected to have inadequate financial literacy. Therefore, increasing financial literacy for them is strategic in order to realize equitable development outcomes for all. This community service aims to provide financial literacy training to 20 farmers in Karangbayan village, West Lombok district. The training method uses an adult learning approach, where the learning materials and processes provide active learning, problem solving, appropriate, and related to the emotional and living atmosphere of participants. The results of the activities include: increasing participants' knowledge and understanding of financial institutions and available financial products, the time value of money (inflation and interest rates), and family financial planning. Furthermore, it is also hoped that there will be an increase in the ability of participants in making financial decisions which is then followed by an increase in the efficiency of the use of financial resources of their families. The conclusion of the activity is that the training has succeeded in increasing the financial literacy of participants so that they are able to make better financial management decisions and have the potential to improve the economic welfare of their families.